Sholat Sebagai Terapi Spritual: Studi Kasus Pada Penderita Stress dan Depresi - N, Nurmaini (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Islam is the second largest religion in the world, which means that many people in the world are Muslim. With the large number of Muslims (followers of Islam), it is urgent for psychology or mental health practitioners to provide services that are appropriate for Muslims. The therapeutic approach as a psychological service for Muslims can be done with a religious approach (psychoreligion) especially with their worship practices. Prayer is one of the worship practices that can provide many psychological benefits for Muslims who carry it out, including relieving stress, increasing subjective well-being, interpersonal sensitivity and others. So that prayer can be an alternative psychotherapy for Muslim patients as a therapeutic process that helps improve their mental health. This article aims to integrate religiosity and psychotherapy.